A percepção dos sons nas diferentes fases da vida - Brito, Cesar Batista de [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
O objetivo do trabalho foi comparar as associações entre acordes e emoções, comparando-se crianças e adultos. Cinquenta crianças e adultos foram submetidos a escuta de quatro sons do acorde C (Dó). Após a escuta, associavam os acordes a emojis, representando sentimentos livres, mas comumente associados a felicidade (😊), paixão (😍), tristeza (☹) e repulsa (🤮). Houve um número significativo de sentimentos positivos para o som de Dó e associação negativa no som de Dó diminuto em ambos os grupos. Tanto o som consonante simples quanto o som mais complexo parecem manter os resultados independentemente da idade.

The objective of this work was to compare the associations between chords and emotions, comparing children and adults. Fifty children and adults were submitted to listening to four sounds of the C chord (C). After listening, they associated the chords with emojis, representing free feelings, but commonly associated with happiness (😊), passion (😍), sadness (☹) and disgust (🤮). There was a significant number of positive feelings for the C sound and a negative association for the diminished C sound in both groups. Both the simple consonant sound and the more complex sound seem to maintain the results regardless of age.
The perception of sounds in different stages of life
Keywords: Órgãos do sentido; Audição; Percepção; Vivência musical; Sense organs; Hearing; Perception; Musical experience